THE DOMESTIC RIGHTS OF THE WIFE (Viewed from KH. Husein Muhammad's Thoughts) - Arina Haque; Ahmad Izzuddin; Iffat Maimunah; Wildana Wargadinata; Suo Yan Mei (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2022)
As the queen of the family, the wife is a determinant of household harmony who understands every detail of her domestic realm. But in fact, several social traditions and norms under the guise of religion limit the space for wives to move in their palaces. This study aims to reveal Husein Muhammad's thoughts on domestic rights in the household and to analyze his mindset in doing istinbath. The method used is literature study in the study of thought. This descriptive qualitative research used the main data sources in the form of two books by Kyai Husein, namely: (1) Women's Fiqh: Kyai's Reflections on the Interpretation of Religious and Gender Discourses published by LKiS in 2019; and (2) Islam, Religion Friendly to Women: Defending Kyai Pesantren, published by LKiS in 2009. Data collection techniques tend to be qualitative with literature documentation techniques. Therefore, an analysis of Kyai Husein's istinbath mindset was carried out using a deductive mindset approach. The results of this study are: (1) The wife has several domestic rights in the household, including the right to support, the right to be the head of the household, the right to express an opinion, the right to mu'asyarah bi al-ma'ruf, and the right to get health services; (2) The mindset of Kyai Husein Muhammad in determining legal istinbath departs from the postulates of sharia with cultural contextualization which then gave birth to the principles of justice and human equality, the concept of sharia as a cultural reflection, and emancipatory jurisprudence.